The Role of Biological Asset Disclosure and Biological Asset Intensity in Influencing Firm Performance - Evy Rahman Utami; Aji Prabaswara (Universitas Muhammadiyah Yogyakarta, Indonesia, 2020)
Abstract:Research aims: The purpose of this study is to analyze the effect of biological asset intensity towards the company performance with biological asset disclosure as an intervening variable.Design/Methodology/Approach: The sample used in this study was firms engaged in the agricultural sector registered in Indonesia Stock Exchange 2015-2017 period. The sample selection method used was purposive sampling according to the required criteria. The analytical tools employed a mediation model based on path analysis using the software process.Research findings: The study results showed that biological asset intensity positively affected biological asset disclosure, biological asset intensity negatively affected the company performance, the biological asset disclosure positively affected the company performance, and the biological asset disclosure mediated the correlation between biological asset intensity and company performance.Theoretical contribution/ Originality: The biological asset disclosure mediated the correlation between biological asset intensity and company performance.Practitioner/Policy implication: This study is expected to encourage firms to be more concerned about biological asset disclosure to improve company performance. On the other hand, this study also helps the standard board see the biological asset disclosure in Indonesia considerably and develop the Indonesian Financial Accounting Standards Guidelines 69.Research limitation/Implication: This study used the Indonesian Financial Accounting Standards Guidelines 69, which is relatively new for companies that effectively implement these regulations.